ACTIVITY PECULIARITIES OF MUSICAL-AESTHETICAL TRAINING OF CHORAL SINGING OF HIGHER CLASSES STUDENTS - Jareckaitė, Stanislava (Acta Paedagogica Vilnensia, 2008)
The basis of this article is a scientific inquiry whose object is musical-aesthetical training activity of choral singing of higher classes students. The aim of this research is to reveal pedagogical-psychological factors influencing the efficiency of musical-aesthetical training of choral singing of higher classes students. We understand students’ musical-aesthetical training by choral singing as the purposeful and expedient formation of personality’s musical-aesthetical relation to art and reality phenomena, musical-aesthetical need and musical-aesthetical-practical activity. The activity of musical-aesthetical choral singing should be described as the complex of the following components: 1) cognitive (knowledge, capability, abilities); 2) valuable-emotional (musical aesthetical needs, interests, aesthetical taste and ideal, motives of musical-aesthetical activity, valuable orientations etc.); will (aspiration, wish to join the activity, singleness of a real behaviour, changing plans etc.) Musical-aesthetical training by the activity of choral-singing of higher classes students in comprehensive schools have a positive purpose however in the primary stage of choir activity, not related to cognitive musical-aesthetical experience, the students of higher classes reveal a negative or neutral valuableemotional relation and behaviour. Neutral and negative valuable-emotional behaviour and relation is revealed especially brightly in boys depending on: 1) age; 2) level of the artistic performance of choir; 3) experience of singing in choirs; 4) musical education; The process of musical-aesthetical training by choir singing of higher classes students reguires the following components: cognitive, valuable-emotional and intercommunion of will and their activization.
Keywords: musical-aesthetical training; choral singing; higher classes students; interests